(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
An association was carried out to study selected different angles of various joint with the performance of jump shot high in team handball. For this research 08 male handball players of LNIPE Gwalior of age 20 ±5, subject were selected on the basis of purposive sampling. The Pearson’s product moment correlation was used in order to find out the association between selected different angles of various joint with the performance Jump shot high in team handball. For testing the hypothesis the level of significance was set at 0.05 where it was hypothesized that there may be significant association between selected different angles of various joint with the performance Jump shot high in team handball. For this ten different part of joint like Ankle Joint (Left), Ankle Joint (Right), Knee Joint (Left), Knee Joint (Right), Hip Joint (Left), Hip Joint (Right), Shoulder Joint (Left), Shoulder Joint (Right), Elbow Joint (Left) and Elbow Joint (Right) was taken to see the association with the performance of jump shot high in team handball. After applying product moment correlation the required value of coefficient correlation for 6 degree of freedom to be significant at 0.05 level is 0.707 and the obtained values were less than, therefore, the selected angles of various joint at Moment Execution and Moment Take-off have exhibited no significant association with the performance of subjects in Jump shot high. Therefore the research study revealed that there is no significant association between the selected different angles of various joint with the performance of jump shot high in team handball.